Ecologia da comunidade de metazoários parasitos do dourado, Coryphaena hippurus Linnaeus, 1758, (Osteichthyes: Coryphaenidae) do litoral do Estado do Rio de Janeiro, Brasil. - Marques, Livia Castro; Alves, Dimitri Ramos (Cadernos UniFOA, 2017)
From April 2009 and July 2010, 68 specimens of common dolphinfish Coryphaena hippurus Linnaeus, 1758 (Osteichthyes: Coryphaenidae) collected from coast of the state of Rio de Janeiro (21-23° S, 41-45° W), were necropsied to study their infracommunities of metazoan parasites. Seventeen species of metazoan parasites were collected. All fish were parasitized by one or more metazoan. The digeneans were the majority of the specimens collected, with 90.7%. Dinurus tornatus (Rudolphi, 1819) was the dominant species with highest abundance, prevalence, frequency of dominance and mean relative dominance. The parasites species of C. hippurus showed a typical aggregate pattern of distribution. None metazoan parasites species showed correlation between total length and prevalence and parasite abundance. The metazoan parasite infracommunities C. hippurus showed dominance of endoparasites (digeneans) and no correlation between abundance and parasite species richness and the total length of the host.